Association of hand and knee osteoarthritis: evidence for a polyarticular disease subset. Issue 1 (January 1996) - Hirsch, R; Lethbridge-Cejku, M; Scott, W W; Reichle, R; Plato, C C; Tobin, J; Hochberg, M C
Abstract : OBJECTIVE--To examine the association between hand and knee osteoarthritis (OA) in a community based population. METHODS--Radiographs of 695 participants aged > or = 40 years in the Baltimore Longitudinal Study of Aging were read for changes of OA, using Kellgren-Lawrence grade > or = 2 as the case definition. RESULTS--Logistic regression analyses, adjusting for age, gender and body mass index, revealed a significant association between OA in the knee and the following joint groups: distal and proximal interphalangeal (DIP, PIP) and Hand2 (OA in two or more hand joint groups) for grade 2-4 and grade 3-4 disease, and the first carpometacarpal (CMC1) joint for grade 3-4 disease. CONCLUSION--There is an association between OA in hand sites and the knee. The strength of the associations increases with increasing disease severity. For the PIP site, there is a trend toward increasing strength of association for increasing numbers of affected joints and bilateral disease.